Modulation of Signal Strength Switches Notch from an Inducer of T Cells to an Inducer of ILC2 - Gentek, Rebecca; Munneke, J. M.; Helbig, Christina; Blom, Bianca; Hazenberg, Mette D.; Spits, Hergen; Amsen, Derk (Frontiers in Immunology, 2013)
Innate lymphoid cells (ILC) are emerging key players of the immune system with close lineage relationship to T cells. ILC2 play an important role in protective immunity against multicellular parasites, but are also involved in the pathogenesis of type 2 immune diseases. Here, we have studied the developmental requirements for human ILC2. We report that ILC2 are present in the thymus of young human donors, possibly reflecting local differentiation. Furthermore, we show that uncommitted lineage-CD34+CD1a- human thymic progenitors have the capacity to develop into ILC2 in vitro under the influence of Notch signaling, either by stimulation with the Notch ligand Delta like 1 (Dll1) or by expression of the active intracellular domain of NOTCH1 (NICD1). The capacity of NICD1 to mobilize the ILC2 differentiation program was sufficiently potent to override commitment to the T cell lineage in CD34+CD1a+ progenitors and force them into the ILC2 lineage. As Notch is an important factor also for T cell development, these results raise the question how one and the same signaling pathway can elicit such distinct developmental outcomes from the same precursors. We provide evidence that Notch signal strength is a critical determinant in this decision: by tuning signal amplitude, Notch can be converted from a T cell inducer (low signal strength) to an ILC2 inducer (high signal strength). Thus, this study enhances our understanding of human ILC2 development and identifies a mechanism determining specificity of Notch signal output during T cell and ILC2 differentiation.